(untitled) (Journal of Medical & Health Sciences Review, 2025)
Introduction: Colorectal cancer (CRC) is the third most prevalent cancer worldwide, and urinary bladder cancer (BC) ranks as the tenth most common. Chronic inflammation has been recognized as a significant contributor to cancer development. Diets rich in red and processed meats, sugars, refined grains, and saturated fats—collectively referred to as pro-inflammatory diets—are known to promote systemic inflammation, which may influence cancer risk. Methodology: This review aims to explore the association between pro-inflammatory diets and the risk of CRC and BC using dietary inflammatory scores: the Dietary Inflammatory Index (DII) and the Empirical Dietary Inflammatory Index (EDII). A systematic search was conducted in PubMed up to October 2022. Human epidemiological studies that employed DII or EDII scores and reported effect estimates (OR, HR, or RR with 95% CI) for CRC or BC were included. A total of 19 studies met the inclusion criteria. Results: Ten case-control and four cohort studies assessed the link between pro-inflammatory diets and CRC, all reporting a positive association. For BC, two case-control studies demonstrated a positive link, while three cohort studies did not find a statistically significant relationship. Conclusion: There is consistent evidence supporting a strong positive association between pro-inflammatory diets and increased CRC risk. However, findings related to BC are inconclusive, with conflicting results between study types. Further large-scale prospective studies and pragmatic clinical trials are needed, particularly to better understand the dietary impact on BC risk and to confirm causality in CRC.